2021
DOI: 10.1021/acsomega.1c00448
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Lignin-Based Carbon Matrix and Carbon Dot Composite Electrodes for High-Performance Supercapacitors

Abstract: This work adopts an efficient chemical-wet method to build a threedimensional (3D) carbon composite as an electrode material for high-performance supercapacitors (SCs). Carbon dots (CDs), prepared by thermal pyrolysis of citric acid and urea under microwaves at 280 °C, are homogeneously coated onto ligninbased activated carbons (ACs), thus forming the 3D composites possessing an interior surface decorated with CD binding sites. Benefiting from the hydrophilicity and ultrafine size of CDs, the affinity of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Recent research has suggested lignin as a sustainable and domestic source for nanostructured hard carbons with far reaching applications in energy storage. Lignin is a highly abundant and renewable resource that possesses high carbon content and an amorphous, cross-linked three-dimensional structure of aromatic polymers . Defining a complete processing–structure–property–performance (PSPP) relationship between lignin and carbonaceous products is difficult because lignin is derived from woody plants and grasses, and the relative fractions of the constituent organic compounds are highly variable by feedstock, which in turn influences the nanostructures and properties of the final carbon composites .…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has suggested lignin as a sustainable and domestic source for nanostructured hard carbons with far reaching applications in energy storage. Lignin is a highly abundant and renewable resource that possesses high carbon content and an amorphous, cross-linked three-dimensional structure of aromatic polymers . Defining a complete processing–structure–property–performance (PSPP) relationship between lignin and carbonaceous products is difficult because lignin is derived from woody plants and grasses, and the relative fractions of the constituent organic compounds are highly variable by feedstock, which in turn influences the nanostructures and properties of the final carbon composites .…”
Section: Introductionmentioning
confidence: 99%
“…The iron serves both as a catalyst for AC formation and a precursor for active magnetic sites. Based on previous work, lignin-based ACs primarily contain a complex microporous structure that limits accessibility to ions. ,, With the impregnation of iron into lignin, surface area and mesopore fraction are greatly improved, thus increasing the porous accessibility toward molecular adsorption in the liquid phase. The adsorption performance of mACs is evaluated by MB dye.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The incorporation of biobased materials into energy technologies comes with significant challenges, usually due to their often disordered and complex nature compared to their inorganic counterparts. Recently, researchers have developed methods to tune these features to their advantage and have made significant strides in the development of nanostructured and bio-based materials for cathodes, [2] electrolytes, [2b,c,3] anodes, [4] super capacitors, [5] and fully organic batteries, [6] resulting in the development of safer, longer lasting, and higher charge density batteries, super capacitors, and fuel cells for use in electric vehicles, mobile electronics, large scale grid applications, and so forth. [7] A primary area of interest lies in generating a sustainable and domestic source of carbon for the energy, manufacturing, and technology industries.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin is an amorphous, cross‐linked structure of aromatic polymers derived from woody plants and grasses and is the world's largest source of renewable carbon. Recent research has stated that lignin can be used to manufacture high quality carbon composites that can be tuned through processing conditions for use in lithium/sodium battery anodes and super capacitors [4a,5,8] . The structure and properties of carbonaceous products manufactured from lignin result from the choice of processing conditions and the relative percentages of the primary monomeric units (syringyl, guaiacyl, and p‐hydroxyphenyl) that constitute lignin [9] .…”
Section: Introductionmentioning
confidence: 99%